Local variation in the timing and advancement of lake ice breakup and impacts on settling dynamics in a migratory waterbird - Pöysä, Hannu (Elsevier, 2022)
Timing of ice-out is important to fundamental hydrological and ecological processes in freshwater ecosystems at high northern latitudes. While earlier ice-out in lakes during the last century is a well-documented phenomenon across the Northern Hemisphere, local variation in the rate of advancement of ice-out has received little attention. Here, records of ice-out date in 1991–2020 from 37 small lakes in a boreal catchment area in southeastern Finland were used to study variation in the timing of ice-out and its advancement. In addition, data of settling phenology of migratory common goldeneyes (Bucephala clangula) at the study lakes were used to examine how between-year and within-season variation in the timing of ice-out affects lake settlement of the species. Overall, ice-out date (IOD, the timing of ice break-up in the spring) advanced 9.8 days during the 30-year study period, April temperature being more important than winter temperature (severity) in determining the IOD. Rate of the advancement of IOD in individual lakes varied from 1.5 to 16.1 days, having advanced more in relatively larger lakes. Lakes at higher elevations had later mean IOD than lakes at lower elevations. Within-season differences among the lakes in IOD increased from 1991 to 2020, this variation being mainly driven by temperature during the ice melting period. Lakes with late mean IOD were settled later in a season by breeding common goldeneyes than lakes with early IOD. The faster the ice melting progressed within a season, the faster common goldeneyes settled the breeding lakes. The results demonstrate how global warming differently affects IOD in boreal lakes even within the same catchment area. More research in the landscape context is needed to enhance our understanding of changes in IOD in boreal lakes and how differently advancing IOD affects local dynamics of species dependent on open water.
Keywords: Aquatic ecosystems; Catchment area; Climate change; Ice-out timing; Spring temperature